2011 14th International IEEE Conference on Intelligent Transportation Systems (ITSC) 2011
DOI: 10.1109/itsc.2011.6082844
|View full text |Cite
|
Sign up to set email alerts
|

Robust traffic signs detection by means of vision and V2I communications

Abstract: This paper presents a complete traffic sign recognition system, including the steps of detection, recognition and tracking. The Hough transform is used as detection method from the information extracted in contour images, while the proposed recognition system is based on Support Vector Machines (SVM), and is able to recognize up to one hundred of the main road signs. Besides a novel solution to the problem of discarding detected signs that do not pertain to the host road is proposed, for that purpose vehicle-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…A comparison of previous studies in detecting the traffic sign is given in Table 4. From Table 5, it can be observed that SVM used in [44] has the highest recall rate with an overall good accuracy of over 90%. 327 signs out of 340 signs are correctly classified.…”
Section: Performance Comparison Of Svm Based Recognitionmentioning
confidence: 97%
See 1 more Smart Citation
“…A comparison of previous studies in detecting the traffic sign is given in Table 4. From Table 5, it can be observed that SVM used in [44] has the highest recall rate with an overall good accuracy of over 90%. 327 signs out of 340 signs are correctly classified.…”
Section: Performance Comparison Of Svm Based Recognitionmentioning
confidence: 97%
“…Support Vector Machine (SVM) is another popular method used by the researchers which is robust against illumination and rotation with a very high accuracy. Yang et al [33] and García-Garrido et al [34] used SVM with Gaussian Kernels for the recognition whereas Park and Kim [35] used an advanced SVM technique that improved the computational time and the accuracy rate for gray scale images.…”
Section: Related Workmentioning
confidence: 99%
“…Overall Accuracy (%) Processing Time (s) [1] 97.60 - [15] 95.71 0.43 [17] 93.60 - [24] 98.62 0.36 [35] 95.20 - [37] 92.47 - [57] 90.27 0.35 [58] 86.70 -Proposed method 99.00 0.28 Figure 15. Real-time experimental results.…”
Section: Referencementioning
confidence: 99%
“…SVM, Neural Network, Hough Transform are the methods that is used by the researchers to minimize the effect of lighting on TSDR system. Neural Network [14][15][16][17][18] AdaBoost [19,20], SVM method for classification [21][22][23][24][25][26] Self-organizing maps (SOM) [27], joint transform correlation (JTC) [28] are the key methods used by different researcher to minimize the effect of various lighting. Many new methods like MSER based HOG [29], The Karhunen-Loeve transform [30], Low Rank Matrix Recovery (LRMR) [31], Fuzzy c means (FCM) [32] are the other machine learning algorithms introduced by the researchers.…”
Section: Current Trends and Challengesmentioning
confidence: 99%